ANALISIS PELAKSANAAN TRI DHARMA PERGURUAN TINGGI DOSEN TEKNOLOGI PENDIDIKAN TAHUN 2019-2024 - Wahyu Sanjaya; Febriati, Farida; Monoarfa, Merrisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was conducted referring to initial observations related to the three aspects of the tri dharma of higher education, where lecturers are expected to make optimal contributions to the development of science, education, research and community service as a whole. This qualitative research aims to analyze how the Tri Dharma of Higher Education Education Technology Lecturers is implemented in 2019 – 2024. This research uses a qualitative approach with a library study type of research. The informants consisted of 10 Educational Technology Lecturers, including the Head of the Educational Technology Study Program, the Secretary of the Educational Technology Study Program and the Head of the Lab. Educational Technology Study Program. Data collection techniques were carried out using interviews, observation and documentation. Data analysis uses data reduction analysis, data presentation and drawing conclusions. The techniques used to check the validity of the data findings in this research are triangulation and member checking. From the research results obtained, namely: 1) education focuses on providing knowledge, developing potential and individual personality, while teaching focuses on building character, expertise and skills. 2) research carried out by lecturers focuses on developing knowledge and solving problems that exist in society. Research usually requires a long time, money and energy, but this research can obtain new information, progress development and also be of significant benefit. 3) Service is one of the lecturers' obligations to contribute to society to improve quality, develop science and overcome problems in society. Of course, every lecturer, in carrying out service, will involve students to help carry out the service, these students function as members. After carrying out service, the lecturer will be responsible for uploading or publishing service activities in National and International journals.